2006
DOI: 10.1111/j.1467-9221.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformed Facial Similarity as a Political Cue: A Preliminary Investigation

Abstract: Experimental subjects evaluated a candidate for local office whose face was digitally altered to absorb the subjects' facial structure. For half of the subjects, the photograph of the candidate was morphed such that the image presented was a blend composed of 60% of the unfamiliar Caucasian male and 40% of the subject. For the other half the photograph was unaltered. Given previous research on implicit familiarity (Zajonc, 1968(Zajonc, , 1980, we predicted that the morph would advantage the candidate. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…In previous research, we have demonstrated that similarity in mediated nonverbal behavior causes high amounts of social influence. Specifically, when one uses digital media to automatically copy head movements (Bailenson and Yee 2005) or handshake styles (Bailenson and Yee 2006), they become more persuasive. Future work should extend these findings to political discourse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous research, we have demonstrated that similarity in mediated nonverbal behavior causes high amounts of social influence. Specifically, when one uses digital media to automatically copy head movements (Bailenson and Yee 2005) or handshake styles (Bailenson and Yee 2006), they become more persuasive. Future work should extend these findings to political discourse.…”
Section: Discussionmentioning
confidence: 99%
“…In our original pilot study, we included a condition in which voters evaluated unaltered images of candidates with no morph at all (Bailenson et al 2006), and demonstrated an advantage for candidates morphed with the self over that unmorphed control condition. The problem with that condition as a control is that the mere act of morphing causes an increase in symmetry and decreases blemishes in faces, two mechanisms known to increase attractiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work we examined the ability of people to detect TSI in digital interactions, ranging from the exchange of simple digital photographs (Bailenson, Garland, Iyengar, & Yee, 2006) to more elaborate CVE contexts (see Bailenson, 2006, for a review). Over dozens of studies, a similar result occurred: People are very poor at detecting transformations of appearance and behaviors during the exchange of digital information.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this facial-similarity manipulation has been tested in a series of studies in voting behavior (Bailenson, Garland , Iyengar, and Yee 2006;Bailenson, Iyengar, Yee, and Collins 2008). In both sets of studies, participants were asked to rate political candidates who either had or had not been morphed with their own photographs.…”
Section: Facial Similaritymentioning
confidence: 99%